Analisis Pola Sebaran Kasus TBC di Jawa Barat Dengan Pendekatan VTMR dan Autokorelasi Spasial - Luh Gde Trishia Damayanti; Ni Wayan Liana Sukmawati; Ni Putu Ananda Puspita Sari; Ni Luh Putu Suciptawati; I Made Eka Dwipayana (Journal on Education, 2024)
The highest Tuberculosis cases were observed in West Java Province. One of the factors are suspected to be the cause is the relationship between neighboring regions. The spread of disease between these areas forms a distribution pattern such as clustered, dispersed, and random which can be detected by the VTMR, Moran's I, and LISA methods. The results of the study with data on Tuberculosis Rates in West Java Province in 2021 showed that with the VTMR method, the distribution pattern of this disease is clustered. Using the spatial autocorrelation such as Moran's I and LISA, it was found that the distribution pattern formed was random. In the LISA test, West Bandung Regency was obtained as a significant area of autocorrelation. While in terms of LISA map visualization, Tasikmalaya, Sukabumi, and West Bandung regencies have a significant effect on the occurrence of spatial patterns. There is a difference in the number of variables that have a significant effect on the calculation in hypothesis testing and GEODA visualization. This indicates that there are variations in spatial patterns between these variables, such as some variables that can form significant groups while others do not.